2017
DOI: 10.1590/1807-3107bor-2017.vol31.0082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ceramic thickness, grinding, and aging on the mechanical behavior of a polycrystalline zirconia

Abstract: Monolithic restorations of Y-TZP have been recommended as a restorative alternative on prosthetic dentistry as it allows a substantial reduction of ceramic thickness, which means a greater preservation of tooth structure. However, the influence of grinding and aging when using a thinner layer of the material is unclear. This investigation aimed to evaluate and compare the effects of ceramic thickness (0.5 mm and 1.0 mm), grinding and aging (low-temperature degradation) on the mechanical behavior and surface ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 36 publications
3
15
0
2
Order By: Relevance
“…Sandblasting and grinding of zirconia surfaces are associated with an energy-induced structural transformation from tetragonal to monoclinic structure which is believed to enhance hydrothermal aging when exposed to dynamic loading in humid environment as described by several authors, including Prado et al [19]. The melt etch method gives less structural transformation [16] and while, according to the present study, improving the adhesion to resin cement.…”
Section: Discussionsupporting
confidence: 61%
“…Sandblasting and grinding of zirconia surfaces are associated with an energy-induced structural transformation from tetragonal to monoclinic structure which is believed to enhance hydrothermal aging when exposed to dynamic loading in humid environment as described by several authors, including Prado et al [19]. The melt etch method gives less structural transformation [16] and while, according to the present study, improving the adhesion to resin cement.…”
Section: Discussionsupporting
confidence: 61%
“…The Weibull statistical analysis was carried out to describe the structural homogeneity of the resin composites tested [13]. The Weibull modulus is usually used as a measure of the distribution of strengths, expressing the reliability of the material [33]. The most reliable composite tested in this study was Concept Advanced (Table 3; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this duality concerns to the standard deviation values of the flexural strength data of the groups (i.e., the data used to calculate the Weibull analyses). Indeed, the Weibull analysis is an effective way to describe the resistance variation of the material [33], and considering that Concept Advanced showed a significant smaller variation of data (SD = 7.5) as compared with Natural Look (SD = 29.8), the former would also present a more reliable structure, which means its structure possesses less likelihood to fracture at small loads when compared to the latter's structure. Concerning the characteristic strength of the composites, Llis showed the strongest behavior, followed by the control and Natural Look, and, lastly, Fill Magic and Concept Advanced.…”
Section: Discussionmentioning
confidence: 99%
“…In 1981, Kobayashi et al first reported this type of degradation caused by aging at 150 to 400°C . Since then, numerous studies have focused on the LTD phenomenon associated with the mechanical properties of zirconia ceramics . Since 2007, the problem of catastrophic failure has been attributed to LTD and transformation of the metastable tetragonal to the monoclinic phase, initiated and accelerated by water penetration …”
mentioning
confidence: 99%
“…8 Since then, numerous studies have focused on the LTD phenomenon associated with the mechanical properties of zirconia ceramics. [9][10][11][12][13] Since 2007, the problem of catastrophic failure has been attributed to LTD and transformation of the metastable tetragonal to the monoclinic phase, initiated and accelerated by water penetration. [14][15][16] At the same time, several factors influence the LTD behavior of zirconia ceramics including size of the stabilizing cation, stabilizer distribution, grain size and stress, surface treatment, and temperature changes.…”
mentioning
confidence: 99%